2002
DOI: 10.1182/blood-2002-03-0789
|View full text |Cite
|
Sign up to set email alerts
|

The role of the D1 domain of the von Willebrand factor propeptide in multimerization of VWF

Abstract: While studying patient plasma containing an unusual pattern of von Willebrand factor (VWF) multimers, we discovered a previously unreported phenomenon: heavy predominance of dimeric VWF. Genomic analysis revealed a new congenital mutation (Tyr87Ser) that altered the final stages of VWF biosynthesis. This mutation in the propeptide (VWFpp) resulted in synthesis of dimeric VWF with an almost complete loss of N-terminal multimerization. The multimer pattern in patient plasma appears to result from separate allele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
77
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(82 citation statements)
references
References 37 publications
5
77
0
Order By: Relevance
“…10,15,37 Several mutations in VWF disrupt multimerization but not regulated storage. 12,16,17 The lack of N528S granular storage is rather distinctive in this regard, although regulated storage has yet to be examined for the majority of the many reported mutations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…10,15,37 Several mutations in VWF disrupt multimerization but not regulated storage. 12,16,17 The lack of N528S granular storage is rather distinctive in this regard, although regulated storage has yet to be examined for the majority of the many reported mutations.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] VWFpp is required for normal VWF multimer assembly and mutations in VWFpp often result in multimerization defects. 12,13 Our previous studies have demonstrated that VWF storage is initiated by VWFpp: VWFpp contains the "signal" for trafficking to granules and secondarily cotraffics mature VWF by virtue of a noncovalent association. 14,15 However, VWF granular storage and multimerization have also been shown to be independent processes: multimerization is not necessary for granular storage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intimate relationship between multimerisation and tubulation, both requiring an interaction of the pro-peptide with the mature protein, may explain why mutations affecting multimerisation can also affect tubulation. For example the clinically significant point mutation within the pro-peptide Y87S, which reduces multimerisation, also reduces WPB elongation when overexpressed against a background of wild-type VWF in HUVECs (Haberichter et al, 2005;Michaux et al, 2006a;Rosenberg et al, 2002). Although it is the storage of VWF as proteinacious tubules within the WPBs, rather than multimerisation, that is responsible for the characteristic elongated shape of the VWF organelle (Michaux et al, 2006a;Wagner et al, 1991), it is very hard to see how such tubules can be assembled from dimers, and much further work in this area is needed.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that vWF plays a critical role in maintaining hemostasis by controlling the assembly of FVIII [25]. To evaluate the binding of FVIII to human plasmavWF and TG pig milk-rhvWF, we measured the capture of FVIII by 200 ng/ml of rhvWF bound to plates.…”
Section: Purification and Analysis Of Rhvwf In Milkmentioning
confidence: 99%